Design and Research of an Eight-bar Back Lifting Mechanism with Single Degree of Freedom - Sun Xuebin; Yu Chengtao; Pan Ao; Gu Cheng; Huang Guangming (Jixie chuandong)
In order to improve the comfort and stability of the separable nursing bed-chair, a new type of eight-bar back lifting mechanism with single degree of freedom is designed. Firstly, combining with ergonomics and taking back slip and slip speed as parameters, it is verified that the back lifting motion of the combined lumbar-back backing plate is more comfortable than that of the traditional single-plate backing plate. Secondly, the kinematics model of the backing mechanism is established, and the parametric model of the mechanism is established in Adams software. Based on this model, the sensitivity of each component to the change of maximum angular acceleration of backing plate during backing process is analyzed, and the key dimensions of the mechanism are optimized with the goal that the maximum angular acceleration of backing plate is the minimum. Furthermore, according to the optimized result, the 3D model of the mechanism is built using the SolidWorks, and the rationality of the mechanism strength is verified by the joint simulation of Adams and Workbench. Finally, a prototype is built to verify the feasibility of the mechanism.